Mutational spectrum and clinical signatures in 114 families with hereditary multiple osteochondromas: insights into molecular properties of selected exostosin variants. (26th February 2019) - Fusco, Carmela; Nardella, Grazia; Fischetto, Rita; Copetti, Massimiliano; Petracca, Antonio; Annunziata, Francesca; Augello, Bartolomeo; D'Asdia, Maria Cecilia; Petrucci, Simona; Mattina, Teresa; Rella, Annalisa; Cassina, Matteo; et al.
Abstract: Hereditary multiple osteochondromas (HMO) is a rare autosomal dominant skeletal disorder, caused by heterozygous variants in either EXT1 or EXT2, which encode proteins involved in the biogenesis of heparan sulphate. Pathogenesis and genotype–phenotype correlations remain poorly understood. We studied 114 HMO families (158 affected individuals) with causative EXT1 or EXT2 variants identified by Sanger sequencing, or multiplex ligation-dependent probe amplification and qPCR. Eighty-seven disease-causative variants (55 novel and 32 known) were identified including frameshift (42%), nonsense (32%), missense (11%), splicing (10%) variants and genomic rearrangements (5%). Informative clinical features were available for 42 EXT1 and 27 EXT2 subjects. Osteochondromas were more frequent in EXT1 as compared to EXT2 patients. Anatomical distribution of lesions showed significant differences based on causative gene. Microscopy analysis for selected EXT1 and EXT2 variants verified that EXT1 and EXT2 mutants failed to co-localize each other and loss Golgi localization by surrounding the nucleus and/or assuming a diffuse intracellular distribution. In a cell viability study, cells expressing EXT1 and EXT2 mutants proliferated more slowly than cells expressing wild-type proteins. This confirms the physiological relevance of EXT1 and EXT2 Golgi co-localization and the key role of these proteins in the cell cycle. Taken together, our data expand genotype–phenotype correlations, offer further insights in the pathogenesis of HMO and open the path to future therapies.